Assessing the Influence of Branding and Promotion Activities to the Business Growth in Rwandan Hotel Industry. A Case of Kigali Serena Hotel - William, Mudahemuka; John, Ntahemuka; Clement, Munyanziza (International Journal for Educational and Vocational Studies, 2020)
Developing countries today compete to attract foreign direct investment to their local hotel industry. Branding and promotion are the ones of the business activities that can assist to the achievement of good performance. Therefore, this study had a general objective of examining the influence of branding and promotion activities to the business growth, case of Serena Hotel. The target population was Serena hotel employees and its customers. The study adopted purposive and simple random sampling methods to select 133 potential respondents. The quantitative data were collected by using administered questionnaires sent to the customers and employees of targeted population and documentary technique have been used for qualitative data collection. Thereafter, statistical techniques have been used to summarize the information. Data from the field were cleaned, sorted, coded, tabulated and statistically analyzed by using SPSS. Among 133 questionnaires sent to the respondents, only 125 were returned for analysis. In data analysis, descriptive statistic was used to compute the frequency and percentages. The results obtained concluded branding and promotion activities were important variables to influence business growth of Serena hotel. As a conclusion, the findings of the study showed that advertising, sales promotions, public relations, personal selling direct marketing and product branding had stronger impact on business growth in Serena Hotel/Rwanda. The recommendations have been given to different domains and the areas for further researches had been identified.